Increased sensitivity to chemically induced colitis in mice harboring a DNA-binding deficient aryl hydrocarbon receptor. (15th December 2022) - Alvik, Karoline; Shao, Peng; Hutin, David; Baglole, Carolyn; Grant, Denis M; Matthews, Jason
Abstract: The aryl hydrocarbon receptor (AHR), a transcription factor best known for mediating toxic responses of environmental pollutants, also integrates metabolic signals to promote anti-inflammatory responses, intestinal homeostasis, and maintain barrier integrity. AHR regulates its target genes through direct DNA-binding to aryl hydrocarbon response elements (AHREs) but also through tethering to other transcription factors in a DNA-binding independent manner. However, it is not known if AHR's anti-inflammatory role in the gut requires its ability to bind to AHREs. To test this, we determined the sensitivity of Ahr dbd/dbd mice, a genetically modified mouse line that express an AHR protein incapable of binding to AHREs, to dextran sulfate sodium (DSS)-induced colitis. Ahr dbd/dbd mice exhibited more severe symptoms of intestinal inflammation than Ahr +/+ mice. None of the Ahr dbd/dbd mice survived after the 5-day DSS followed by 7-day washout period. By day 6, the Ahr dbd/dbd mice had severe body weight loss, shortening of the colon, higher disease index scores, enlarged spleens, and increased expression of several inflammation genes, including interleukin 1b ( Il-1b ), Il-6, Il-17, C-x-c motif chemokine ligand 1 ( Cxcl1 ), Cxcl2, Prostaglandin-endoperoxide synthase ( Ptgs2 ), and lipocalin-2. Our findings show that AHR's DNA-binding domain and ability to bind to AHREs are required to reduce inflammation, maintain a healthy intestinal environment, and protect against DSS-induced colitis.